Implementation of SBAR Communication among Nurses during Handover between Shifts before and after a Mini Seminar in the Mawar Inpatient Ward, West Kalimantan - Ignasius Yogi; Lidya Maryani (Indonesian Journal of Health Research and Development, 2026)
Delayed care processes, lack of attention, and limited knowledge in receiving patient information often lead to poor communication among nurses. The World Health Organization recommends SBAR (Situation, Background, Assessment, Recommendation) as a structured communication tool to convey critical information requiring immediate action. This study aimed to determine the implementation of SBAR communication among nurses during handovers between shifts before and after a mini seminar in the Mawar Inpatient Ward, West Kalimantan. A pre-experimental design with a one-group pretest–posttest approach was applied and described descriptively. The results showed that before the mini seminar, 50% of respondents applied SBAR communication incorrectly, while 50% applied it correctly. After the mini seminar, there was a significant improvement, with 100% of respondents applying SBAR communication appropriately. These findings indicate that the mini seminar successfully improved the implementation of SBAR communication among nurses during shift handovers. In conclusion, the mini seminar was proven to enhance the professionalism of nursing services by optimizing communication, reducing the risk of medical errors, and supporting better quality of care in the inpatient ward.